The correlation between mental health status, sleep quality, and inflammatory markers, virus negative conversion time among patients confirmed with 2019-nCoV during the COVID-19 outbreak in China: An observational study. Issue 27 (9th July 2021) - Li, Xixi; Cai, Quan; Jia, Ziyi; Zhou, Yifang; Liu, Linzi; Zhou, Yuning; Zhang, Baoyan; Ren, Luyu; Tang, Yanqing
Abstract : Abstract: The 2019 coronavirus disease (COVID-19) has spread to the whole world. Psychological and sleep problems among confirmed patients have drawn extensive attention which may be highly related to immune function and inflammatory responses of people. The aim of this study is to examine the correlation of mental health status, sleep quality, and inflammatory markers, virus negative conversion time (NCT) among confirmed patients during the COVID-19 outbreak. A cross-sectional survey was conducted in this study. Data from 66 patients assessed with demographic information, anxious symptom, depressive symptom, stress, and sleep quality were collected using a smartphone-based questionnaire platform and then clinical characteristics and laboratory indicators were collected using case review. Nearly 30% of the participants reported depression, anxiety, perceived pressure, and poor sleep quality. Compared with the group without depression, neutrophil count, and ratio of neutrophil count to lymphocyte count (NLR) in the depression disorder group were increased ( P  = .028, 0.043). There was also a significant difference in NLR and NCT between the anxiety group and the non-anxiety group ( P  = .021, .024). Similarly, compared with the good sleep quality group, NLR in the poor sleep quality group was increased ( P  = .011). Correlation analysis indicated that Self-Rating Depression Scale score was positively related to neutrophil count and NLR ( r  = 0.366, 0.330, P  = .016, .031). The total score of Pittsburgh Sleep Quality Index (PSQI) was negatively related to lymphocyte count ( r  = −0.317, P  = .049), and the sleep disturbance as 1 of the 7 dimensions of PSQI scale was positively correlated with NCT and NLR ( r  = 0.370, 0.340, P  = .020, .034). In our study, confirmed patients were prone to have psychological and sleep problems. The level of inflammation in patients with psychological and sleep problems was higher than that in patients without corresponding problems. The inflammatory level increased with the increase of Self-Rating Depression Scale score, and the lymphocyte count decreased with the increase of the PSQI score. NCT was prolonged in the anxiety group and sleep disturbance was positively correlated with NCT.